Two Profiles of the Polish HOMELAND Concept - Bartmiński, Jerzy (Vilnius University Open Series, 2021)
The starting point for this study is the dynamic view of homeland formulated by e.g. Karol Wojtyła in his Thinking Homeland (“When I think homeland, I seek the road that cuts through mountainsides… it runs steeply up in each of us and does not allow to stand still”). The study focuses on two profiles of the Polish concept: the noble-intelligentsia profile and the folk-peasant profile. In the former, which continues the tradition of military legions, the relationship between people and homeland is modelled in accordance with the patriotic-heroic ethos, deriving from the Romantic tradition and focusing on active resistance and sacrifice. In the latter, the predominant mood is expiatory, connected with the responsibility for the collapase of the the 1st Polish (Nobility) Republic. This profile includes the all-national homeland, then the regional and European homeland – the ideas of the state, civic, and cultural homeland compete with one another. The folk profile of homeland derives from the tradition of Polish peasantry – peasants did not feel responsible for the collapse of the state, being de facto slaves in the Poland of nobility. The peasant ethos, based on the idea of joint work and social solidarity, is close to the positivistic spirit. It links the idea of duty (homeland can ask for sacrifice) with that of expectation (homeland should extend one’s care over people). The folk profile includes the homeland of family and home, the local homeland, the national homeland, as well as the world as people’s homeland. It is assumed that the two profiles of homeland are to a great extent complementary.